RURAL-URBAN MIGRATION FACTORS AND EFFECTS: A COMPARISON STUDY BETWEEN JAKARTA, INDONESIA, AND KLANG VALLEY, MALAYSIA METROPOLITAN - Yuangwidi, Kinanthi Purbaning; Razali, Muhammad Syafiq; Fuad, Fatihin Nabiha Mohd Zekeri; Abdullah, Nurul Hakimah Che; Salma, Greace Nanda Putri; Ashari, Arif; Ervin, Muhamad (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2024)
Cities in Southeast Asia continue to be destinations for population migration in recent years. Large migration destinations include the Klang Valley, Malaysia, and the Jakarta Metropolitan area, Indonesia. Here, we present an analysis of the factors and impacts of rural-urban migration in Klang Valley, Malaysia and Jakarta, Indonesia. The study was conducted using secondary data obtained from desk research and documents. The analysis was conducted descriptively by paying attention to the themes of geography, namely location, place, human and environmental interaction, movement, and region. This research is a qualitative research that implements phenomenology in geography. The results show that rural-urban migration is influenced by several factors, namely economic, social, and government policies related to the metropolitan area development plan. In summary, this study provides alternative information about the causes and impacts of rural-urban migration in metropolitan cities in Southeast Asia. Keywords: Factors, Effects, Rural-Urban Migration, Klang Valley, Jakarta Metropolitan Area